'Keeping Up with Myself': Ethnography of a Young Adult Woman in Post-Transitional Croatia. Issue 1 (1st March 2022) - Peternel, Lana; Maskalan, Ana
Abstract: This article employs an anthropology 'at-home' approach to discuss dimensions of social and cultural changes amongst women in post-transitional societies. By applying person-centred ethnography, we aim to provide rich insights into the socio-cultural context and individual development of a young woman in Croatia. We examine how a young woman reasons about what kind of a person she is and wants to become by comparing the different sets of basic values that she ascribes to her emancipatory efforts, with a focus on how she juxtaposes 'traditional family roles' and 'feminist values'. The article thus describes how this woman (Jadranka) experiences life challenges and shapes social values in her everyday cultural settings.